XG‐102 administered to healthy male volunteers as a single intravenous infusion: a randomized, double‐blind, placebo‐controlled, dose‐escalating study. Issue 1 (26th January 2014) - Deloche, Catherine; Lopez‐Lazaro, Luis; Mouz, Sébastien; Perino, Julien; Abadie, Claire; Combette, Jean‐Marc
Abstract: The aim of the study is to evaluate the safety, tolerability and pharmacokinetics (PK) of the JNK inhibitor XG‐102 in a randomized, double blind, placebo controlled, sequential ascending dose parallel group Phase 1 Study. Three groups of male subjects received as randomly assigned ascending single XG‐102 doses (10, 40, and 80  μ g/kg; 6 subjects per dose) or placebo (2 subjects per dose) as an intravenous (IV) infusion over 60 min. Safety and tolerability were assessed by physical examination, vital signs, electrocardiography, eye examination, clinical laboratory tests and adverse events (AEs). PK was analyzed using noncompartmental methods. All reported AEs were mild to moderate and neither their number nor their distribution by System Organ Class suggest a dose relationship. Only headache and fatigue were considered probably or possibly study drug related. Headache frequency was similar for active and placebo, consequently this was not considered to be drug related but probably to study conditions. The other examinations did not show clinically relevant deviations or trends suggesting a XG‐102 relationship. Geometric mean half‐life was similar among doses, ranging from 0.36 to 0.65 h. Geometric mean XG‐102 AUC0–last increased more than linearly with dose, 90% confidence intervals (CIs) did not overlap for the two highest doses. Geometric mean dose normalized C max values suggest a more than linear increase with dose but 90% CIs overlap. It may be concluded that XG‐102 single IV doses of 10–80  μ g/kg administered over 1 h to healthy male subjects were safe and well tolerated. Abstract : e00020